The Tick-Tock Man - Hamilton, Kersten, 1958- (Hamilton, Kersten, 1958- Gadgets and gears, 2016)
Wally the boy scientist and his sidekick Noodles the dachshund help a pickpocket named Dobbin who works for the mysterious London criminal, the Tick-Tock Man.